Environmental and human health risk assessment of trace metals in the mussel ecosystem from the Southwestern Mediterranean. (February 2020) - Guendouzi, Yassine; Soualili, Dina Lila; Fowler, Scott W.; Boulahdid, Mostefa
Abstract: This study evaluates the geographical distribution of Pb, Cd, Cr, Ni, Co, Cu, Zn, Mn and Fe in wild mussels Mytilus galloprovincialis as well as in associated suspended particulate matter (SPM) and sediments from the Algerian coast. The bioaccumulation (metal concentrations in tissue), bioavailability (metal indices) and bioconcentration of trace metals from the adjacent environment were assessed. The computed pollution load index (PLI) indicates that the sediments are not polluted by these metals, except for Zn which shows a moderate level of contamination. All the metals in SPM samples are in a 'safe range' with respect to the computed degree of contamination (DC < 2). The target hazard quotients (THQ) and the hazard index (HI) values indicate a risk level with Fe. However, the Cr measured in mussels is considered 'extreme', according to the consumption rate limit for mussels (CRlim ) which limits their consumption to 0.5 kg/day. Highlights: Trace metal levels in the Algerian mussel ecosystem were studied. The relationship of metals between sediment, suspended particulate matter and mussels was determined. Cr was the critical metal that posed a potential health risk for mussel consumers.